Toward Green Optoelectronics: Environmental-Friendly Colloidal Quantum Dots Photodetectors - Miao, Sijia; Cho, Yuljae (Frontiers in Energy Research, 2021)
Colloidal quantum dots (CQDs) have attracted tremendous research interests for future generation energy, electronic, optoelectronic and bio-imaging applications due to their fascinating material properties, such as solution processability at room temperature and under ambient conditions, compatibility with various functional materials, and high photo-stability as well as photo-sensitivity. Among various optoelectronic applications of CQDs, in particular, optical light sensors which convert photonic energy into electrical signals have been of particular interests because they are one of the key building blocks for modern communication and imaging applications including medical X-ray and near-infrared imaging, visible light cameras, and machine vision. However, CQDs, which have been widely researched for photodetectors so far, contain toxic and hazardous heavy metals, namely, lead (Pb), cadmium (Cd), and mercury (Hg). These substances are extremely toxic and harmful to the environment as well as human beings. Therefore, it is highly desirable to substitute CQDs containing the heavy metals with non-toxic and environmentally friendly ones to realize green optoelectronics. In this review article, we introduce various kinds of heavy metal free CQDs and their applications to photodetectors. The article comprehensively includes working mechanisms of the photodetector, various kinds of non-toxic and environmentally friendly CQDs-based photodetectors, advanced heterojunction photodetectors, and discussion for future perspectives.